DetOx: a program for determining anomalous scattering factors of mixed-oxidation-state species - Sutton, K; Barnett, S; Christensen, K; Nowell, H; Thompson, A; Allan, D; Cooper, R (International Union of Crystallography, 2013)
Overlapping absorption edges will occur when an element is present in multiple oxidation states within a material. DetOx is a program for partitioning overlapping X-ray absorption spectra into contributions from individual atomic species and computing the dependence of the anomalous scattering factors on X-ray energy. It is demonstrated how these results can be used in combination with X-ray diffraction data to determine the oxidation state of ions at specific sites in a mixed-valance material, GaCl₂.